Hypothalamic-pituitary-adrenal-axis vs. the sympatho-adrenal medullary system in the acute response to psychological stress - Janse van Vuuren, Marthinus (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2011.